Pengembangan Media Pembelajaran Permainan Ludo Fisika pada Pokok Bahasan Alat Optik untuk Meningkatkan Kolaborasi Siswa - Novianti; Siti Anisatur Rofiqah; Arini Rosa Sinensis (Pendidikan Fisika Universitas Nurul Huda, 2022)
The purpose of this study was to develop ludo physics learning media and analyze the impact of ludo games on improving students' collaboration skills. This study used the Research and Development (R&D) method with the borg & gall procedural model. The results of this study are: (1) Ludo physics game learning media (2) Ludo physics game learning media the final product produced meets the feasible criteria with a score of 2 expert lecturers in the media field with an average percentage rating of 90.43% in the very feasible category, and the assessment of 2 teachers who are experts in the field of material with an average percentage of 94.63% in the very decent category. (3) The feasibility of the product in the learning media for the ludo physics game, the average feasibility of the display of the ludo physics learning media is 84.25% in the very interesting category and for the percentage of feasibility in the function of the ludo physics learning media, it is 80.86% in the very interesting category. This learning media is